The role of brown and beige adipose tissue in glycaemic control - Klepac, Katarina; Georgiadi, Anastasia; Tschöp, Matthias; Herzig, Stephan (Molecular aspects of medicine, 2019)
For the past decade, brown adipose tissue (BAT) has been extensively studied as a potential therapy for obesity and metabolic diseases due to its thermogenic and glucose-consuming properties. It is now clear that the function of BAT goes beyond heat production, as it also plays an important endocrine role by secreting the so-called batokines to communicate with other metabolic tissues and regulate systemic energy homeostasis. However, despite numerous studies showing the benefits of BAT in rodents, it is still not clear whether recruitment of BAT can be utilized to treat human patients. Here, we review the advances on understanding the role of BAT in metabolism and its benefits on glucose and lipid homeostasis in both humans and rodents. Moreover, we discuss the latest methodological approaches to assess the contribution of BAT to human metabolism as well as the possibility to target BAT, pharmacologically or by lifestyle adaptations, to treat metabolic disorders.
Gesehen am 20.12.2021